Localization and Micromorphological Structure of the Lingual Tonsil in Goat (Capra hircus) - Saran, Devendra; Singh, Opinder; Pathak, Devendra (Indian Journal of Veterinary Anatomy, 2023)
The present study was undertaken on (n = 24) adult unidentified breed of goat to elucidate the gross anatomical and micromorphological structure of the lingual tonsil. The lingual tonsils were not observed grossly. The largest lymphoid aggregations were seen in the connective tissue core of the circumvallate papilla. The aggregated lymphocytes within the connective tissue core of the circumvallate papilla were not encapsulated. The circumvallate papilla was lined by stratified squamous keratinized epithelium with taste buds. The epithelium was made up of three layers: basale, spinosum with some cells having keratohyaline granules in upper layer, and comeum. The average height of the epithelium of circumvallate papilla was observed at 81.441±2.642µm. The collagen and reticular fibers formed a connective tissue framework around lymphocytes. Elastic fibers were observed in the layer oftunica intima ofblood vessels.